Prepublication data sharing. - Birney, E; Hudson, T; Green, E; Gunter, C; Eddy, S; Rogers, J; Harris, J; Ehrlich, S; Apweiler, R; Austin, C; Berglund, L; Bobrow, M; et al. (2009)
Rapid release of prepublication data has served the field of genomics well. Attendees at a workshop in Toronto recommend extending the practice to other biological data sets.